Parenting Education on Children’s Sexual Education: A Quranic Content Analysis - Eramahi, Eka; Hasnan, Hasnan; Ridha, Arif (STIT Ahlussunnah Bukittinggi, 2025)
Sexual education is a conscious and systematic effort carried out within the family, school, and community to provide children with an understanding of reproductive organs while instilling moral, ethical, and religious commitments to prevent sexual abuse and misconduct. This study aims to explore and conceptualize parenting education related to children’s sexual education from a Quranic perspective in order to enhance children’s responsibility and self-protection against sexual violations. The study employed a qualitative approach using content analysis, drawing data from relevant books, academic journals, and scholarly articles that are thematically aligned with the research focus. The findings reveal six core themes of parenting education on children’s sexual education from the Quranic perspective: (1) ethics of privacy and seeking permission (isti’dhān), (2) lowering the gaze and covering ‘awrah, (3) social interaction boundaries and the prohibition of adultery, (4) self-restraint and chastity (‘iffah), (5) understanding maḥram relationships, and (6) character formation in sexuality. These findings contribute conceptually to the discourse on Islamic parenting and may serve as a foundational reference for future studies examining children’s sexual education in different contexts and issues.